Integration and continuity of primary care : polyclinics and alternatives – a patient-centred analysis of how organisation constrains care co-ordination /: polyclinics and alternatives – a patient-centred analysis of how organisation constrains care co-ordination. (August 2015) - Sheaff, Rod
No abstract available